PENGUJIAN TURBIN ANGIN DENGAN VARIASI KECEPATAN ANGIN, PUTARAN MOTOR DAN PUTARAN GENERATOR DENGAN MENGGUNAKAN TEROWONGAN ANGIN JENIS HORIZONTAL 3 BLADE - Sulaiman, Sulaiman; Gunawan, April (ITP Press, 2023)
Where wind is used at speeds of 3,4,5 and 6 m/s .Blade type with pine wood material,with Naca 4412,blade Naca 4412 with 70% epoxsy resin + 30 % glass fiber,Naca blade 4412 with 70% epoxsy resin + 18% glass fiber + 12% coconut fiber,Naca blade 4712 with 70% epoxsy resin+ 18% glass fiber + 12% coconut fiber and Naca 5513 blade with 70% epoxsy resin+ 18% glass fiber+ 12% coconut fiber.Blade type epoxsy resin+ fiber glass + coir Naca 4412 blade has the highest rotation compared to other blade types that have been in the test.Where the generator rotation at awind speed of 3 m/s generator rotation has been calculated to reach an average of 545.29 rpm,a wind speed of 4 m/s generator rotation is 708.9 rpm,and at a wind speed of 5 m/s the generator rotation is 928.94 rpm, and at wind speed of 6 m/s the generator rotates at 928.94 rpm.